MEDIA PEWARISAN PENGETAHUAN LOKAL MITIGASI GEMPA BERBASIS ARSITEKTUR BALE BELEQ SASAK SEGENTER DAN GUMANTER - Dodik Kariadi; Wasis Suprapto; Slamat Fitriyadi; Gustin M.Pd (MEDIOVA: Journal of Islamic Media Studies, 2022)
The research departs from the fact that the level of knowledge and skills of students in dealing with the earthquake in Lombok is low. Meanwhile, social science learning in schools does not contribute to the formation of students' knowledge and skills in dealing with earthquakes. In fact, the island of Lombok is an area with a high level of vulnerability to earthquake disasters in Indonesia. Thus, in this study, the main objective is to develop earthquake mitigation media sourced from the Sasak indigenous people themselves and allotment for schools in Lombok. The research method used is a research and development approach. From the research and development process, several results were obtained including: First, the more effective the learning process for teachers and students because they used earthquake mitigation media based on values ​​that existed in the Sasak community themselves; Second, the results of both quantitative and qualitative analysis show that earthquake mitigation media based on the value of the bale beleq architecture are able to improve the school's mitigation capability against earthquake disasters. So with the architectural value-based mitigation media that exists in the Sasak community itself, teachers and students are more effective and efficient in order to improve the ability of earthquake disaster mitigation in schools. Keywords: Media, Knowledge, Mitigation, Architecture.